A devotee in a state of trance during aarti - Mumbai Archive Project Team (Jio Institute, 2024)
A devotee in a state of trance during aarti (the ritual of waving the sacred fire in front of the deity). The aarti ceremony is a communal activity, often involving the entire neighbourhood, and performed by elder members of the family.